E-book of poem collections / Nor Zerina Johanudin … [et al.] - Johanudin, Nor Zerina; Misman, Juritah; Mohd Zain, Zainab; Abd Rahman, Nur Fatin Nabila; Ramlan, Aini Faezah; Nik Abdullah, Nik Narimah (Academy of Language Studies, 2023)
E-books nowadays have been one of the contemporary mediums of literary materials where users share their knowledge online. This E-book focuses on the compilation of poems that showcased the potential talents of language students from Universiti Teknologi MARA (UiTM) and also the subject called Creative Writing. This project engages readers to write and also learn more about the English language. Furthermore, this E-book consists of 10 different poems written by various authors. The poems are complemented by picturesque designs and the spectacular essence of poem writing. Besides that, the poems come together with an author's columns which explain the thoughts behind the poems. It is hoped that readers would better understand the true feelings and inspiration of the poets.